Hybridization and How It Takes Place: The Case of Batak Students in Jember - Ines Christy Simarmata, Ines Christy; Dodik Harnadi, Dodik Harnadi; Mohammad Rifan Firmansyah, Mohammad Rifan (Rumah Jurnal, University of Jember, 2025)
This research aims to understand the process of identity formation among regional students in Jember District. The subjects of this study are Batak ethnic regional students from North Sumatra who have resided in Jember District for more than two years. The theoretical framework employed for analyzing this phenomenon is Stuart Hall's theory of hybrid identity. Employing data collection methods such as interviews, observations, and documentation, the findings reveal that the process of hybrid identity formation among Batak ethnic regional students in Jember District is shaped through interactions within public spaces, such as campus environments and surrounding environments. Cultural differences between the objects and the local Jember community frequently result in dynamics within the adaptation process. Consequently, these students must open themselves up to accept and adopt certain elements of the Pandalungan culture, which represents a form of hybridity of the local multicultural Jember community. This leads to a blending of identities, producing a hybrid identity that is reflected in language, etiquette, and culinary. Nevertheless, Batak ethnic regional students in Jember Regency maintain aspects of their authentic identity, such as their clan (marga), Batak language, mardebata (rituals or prayers), and martutur (kindship relationships). This study expounds that the hybrid identity of regional students is continually in a state of 'becoming'.